AHCYL1 Is a Novel Biomarker for Predicting Prognosis and Immunotherapy Response in Colorectal Cancer. (7th May 2022) - Li, Xubin; Zhang, Mengqiao; Yu, Xue; Xue, Mei; Li, Xiaowei; Ma, Chao; Jia, Wei; Gao, Qiang; Kang, Chunbo
Abstract : Background . Colorectal cancer (CRC) is the third most frequent cancer worldwide. The AHCYL1 gene is required for CNV and has a close association with the tumor immune microenvironment. However, the predictive value of the AHCYL1 gene in patients with CRC remains unknown. Methods . AHCYL1 gene with prognostic potential was comprehensively analyzed. Next, using LASSO Cox regression, we fully examined and integrated the AHCYL1 and AHCYL1-related genes from TCGA database. Meanwhile, TCGA database was used to study the connection between AHCYL1 and the tumor immune microenvironment and tumor mutation burden (TMB) in CRC. The influence of AHCYL1 in tumor growth and the recruiting ability of CD8+ T cells were verified, respectively, in vivo and in tissues. To ascertain the connection between AHCYL1 and AHCYL1-related genes and the prognosis of CRC, a prognostic model was created and validated. Result . We demonstrated that AHCYL1 has a differential expression and patients with AHCYL1 deletion get shorter survival in CRC. Additionally, the tissues without AHCYL1 have a weaker ability to recruit the natural killer (NK) cell, CD8+ T cells, and tumor-infiltrating lymphocytes (TILs) and response to immunotherapy. Additionally, knockdown of AHCYL1 promoted tumor growth in the CRC mouse model and recruited lower CD8+ T cells in CRC tissues. TCGA database was used to classify patients into low- and high-risk categories based on the expression of four genes. Meanwhile, we discovered an association between the low-risk group and a lower TMB and a higher response to immunotherapy. Finally, a predictive nomogram based on these genes was developed and verified, yielding a C-index of 0.74. Conclusion . For CRC patients, the prognostic model based on AHCYL1 and AHCYL1-related genes showed a high predictive performance in terms of prognosis and immunotherapy response.